Composite structures of steel and concrete : beams, slabs, columns, and frames for buildings - Johnson, R. P. (Roger Paul) (Malden, MA : Blackwell Pub., 2004)
This book sets out the basic principles of composite construction with reference to beams, slabs, columns and frames, and their applications to building structures. It deals with the problems likely to arise in the design of composite members in buildings, and relates basic theory to the design approach of Eurocodes 2, 3 and 4. The new edition is based for the first time on the finalised Eurocode for steel/concrete composite structures.
Contents; Preface; Symbols, terminology and units; Chapter 1 Introduction; Chapter 2 Shear connection; Chapter 3 Simply-supported composite slabs and beams; Chapter 4 Continuous beams and slabs, and beams in frames; Chapter 5 Composite columns and frames; Appendix A Partial-interaction theory; A.1 Theory for simply-supported beam; A.2 Example: partial interaction; References; Index.
Includes bibliographical references and index.
Keywords: Composite construction; Building, Iron and steel; Concrete construction